Comparing teachers and medical students as trainers of cardiopulmonary resuscitation (CPR) among secondary school students - Mohd Hisham Mohd Isa; Shamsuriani Md Jamal; Afliza Abu Bakar; Tan, TL; Dazlin Masdiana Sabardin; Fadzlon Mohd Yatim; Siti Nidzwani Mohamad Mahdi; Emilia MR; Nik Azlan Nik Muhamad (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Bystander rate of cardiopulmonary resuscitation (CPR) is still low worldwide because of inadequate skills and knowledge. Training the public on CPR is one of the methods to increase the bystander CPR rate. This study aimed to compare the efficacy in acquiring and retaining CPR skills and knowledge among secondary school students in Klang Valley trained by school teachers and medical students. We recruited five school teachers and five medical students as trainers. They were trained in several sessions by American Heart Association (AHA)-certified instructors using the video-assisted CPR training module. The recipients were 44 secondary school students divided between the teacher’s group and the medical student’s group. We compared knowledge and psychomotor skills between these two groups prior, immediately after and at three months after CPR training. Students in the teacher’s group showed a higher increase in knowledge comparable to the medical student’s group (median score difference 3 vs 2, p>0.05) and in psychomotor skill (median score difference 5 vs. 7, p<0.05). The level of knowledge and skills decreased after 3 months but remained significantly higher than at baseline for both groups. In conclusion, teachers could provide CPR training to their students as effective and retainable as medical students. This study aims to create an opportunity to teach CPR to the public in a larger scale.